Improving rural development planning and management: Proceedings of IICA-PORPLAN/ USDA-DPMC Seminar - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
240 páginas. Proplan Documento 18. Serie Papers, conclusions and recomendations from technical events 265.